The correlation between transcription factor 7-like 2 gene polymorphisms and susceptibility of gestational diabetes mellitus in the population of central China: A case–control study - Zhang, Pei; Deng, Mengyao; Li, Wei; Dai, Qiong; He, Hua; Zheng, Wenpei; She, Lu; Xiang, Bing; Zeng, Jing; Zhou, Feng; Guo, Yan; Yang, Mei (Frontiers in Endocrinology, 2022)
Objective: To investigate the correlation between transcription factor 7-like 2 (TCF7L2) gene polymorphism and gestational diabetes mellitus (GDM) risk in central Chinese populations. Methods: This case-control study examined the association of 7 TCF7L2 gene SNPs (rs11196218, rs4506565, rs7895340, rs7901695, rs11196205, rs12243326 and rs290487) with GDM risk in central Chinese populations (843 GDM and 877 controls). The clinical information and blood samples were collected by trained interviewers and nurses. Genotyping of SNPs was conducted on the Sequenom MassARRAY platform. Statistical analyses including t-test, ANOVA, chi-square test, fisher exact test and logistic regression were performed. Results: Differences in age, pre-pregnant BMI, family history of type 2 diabetes mellitus (T2DM) between the case and control groups were significant (P<0.05). Compared with the wild genotype, pregnant women with genotypes of rs4506565 AT (OR=1.89, 95%CI:1.18-3.02), rs7895340 GA (OR=1.93, 95%CI:1.06-3.54), rs7901695 TC (OR=1.79, 95%CI:1.11-2.88) and rs11196205 GC (OR=2.15, 95%CI:1.16-3.98) had significantly higher risk of GDM, adjusted by age, pre-pregnant BMI and family history of T2DM. Functional annotations showed that all these four SNPs fell in the functional elements of human pancreatic islets. Further cumulative effects analysis concluded that when participants carried all these four risk genotypes, the risk of GDM was 3.51 times (OR=3.51, 95%CI:1.38-8.90) than that of those without any risk genotypes. Conclusions: The findings of this study suggested that the TCF7L2 gene SNPs rs4506565, rs7895340, rs7901695 and rs11196205 were genetic susceptibility SNPs to GDM in the central Chinese population. Further studies are needed to validate our findings and clarify the underlying mechanisms.